Numerical simulation of free convection of MHD non-Newtonian nanofluid within a square wavy enclosure using Meshfree method. Issue 1 (9th November 2020) - Jain, Sapna; Bhargava, Rama
Abstract: In this article, flow and heat transfer of nanofluids inside a wavy square enclosure filled with non-Newtonian (shear thinning) nanofluid under magnetic field has been simulated numerically. Single-phase model is used. The governing equations have been solved numerically using element free Galerkin method. The results are obtained for isotherms, streamlines, and average Nusselt number for various values of Hartmann number, Rayleigh number, nanoparticles volume fraction, and power-law index. Here, the main objective is to explore the effect of power-law index, Rayleigh number, Hartmann number, and volume fraction on average Nusselt number. It is found that in the absence of magnetic field, Nusselt number drops on increasing the value of power-law index whereas in the presence of magnetic field, heat transfer rate increases with increase in power-law index. With the increase in Rayleigh number and volume fraction of nanoparticles, the heat transfer rate increase in all cases. This type of problem has a direct application in the coolant systems, solar collector where the structure used is wavy in order to increase the rate of heat flow. Here, EFGM is efficiently applied for simulation due to irregular domain, which creates a novelty in the work.